Analysis of the Psychoeducational Intervention Models in Students with Autism Spectrum Disorder - Rúa, Manuel Ojea (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
This research consists of a comparative analysis of the results obtained in the development of students with autism spectrum disorders (ASD) found as a consequence of the application of three basic models of educational guidance: 1) the social mediation model; 2) the counselling model; and 3) the service model, delivered through services developed over three years, distributed across three experimental groups corresponding to each of these guidance models. A total of N: 18 students with ASD of different levels, ages and genders have participated in the study, assigned to one of the three following groups: a social mediation model group, a counselling model group and a services model group. Study of the data was undertaken by analysing the multivariate contrasts of repeated measures ANOVA for a factor of three measures, both for the variable group types (three groups), as well as for the participants’ level, age and gender variables. The results show the statistically significant benefits of the social mediation model.